Social Media in an English Village : (Or how to keep people at just the right distance) - Miller, Daniel (Book collections on Project MUSE., 2016)
Daniel Miller spent 18 months undertaking an ethnographic study with the residents of an English village, tracking their use of the different social media platforms. Following his study, he argues that a focus on platforms such as Facebook, Twitter and Instagram does little to explain what we post on social media. Instead, the key to understanding how people in an English village use social media is to appreciate just how 'English' their usage has become. He introduces the 'Goldilocks Strategy': how villagers use social media to calibrate precise levels of interaction ensuring that each relationship is neither too cold nor too hot, but 'just right'.